Optimalisasi Pengembangan Desa Sebidai Menuju Desa Mandiri Melalui Program Kuliah Kerja Nyata (KKN) - Nurjannatul Hasanah; Rahmi Nur Islami; Ahmad Fuad Hasim (Indonesia Bergerak : Jurnal Hasil Kegiatan Pengabdian Masyarakat, 2025)
One of the mandatory programs for students of Borneo Tarakan University is the Real Work Lecture (KKN) by combining students from various departments into one group placed in a village to carry out community service. Group 19 was placed in Sebidai Village, Tana Tidung with the aim of "Optimizing Village Development towards Independent Villages". The problems were the lack of public understanding about proper agricultural land clearing, the low knowledge in managing agricultural products (taro) into superior products, and the lack of village understanding regarding fair and reasonable retribution. The activities included socialization on the dangers of illegal land clearing, entrepreneurship training on processing taro into marketable chips and cakes, as well as the proposal of village regulations regarding retribution. The results of the activities had a positive impact, with the community being more vigilant in land clearing, taro-based products being able to be marketed, and village regulations on retribution being completed as requested by the Village Head.